Effect of Age on Outcome of High-Risk Non-Muscle-Invasive Bladder Cancer Patients Treated with Second Transurethral Resection and Maintenance Bacillus Calmette-Guerin Therapy - TİNAY, İLKER (GALENOS YAYINCILIK, 2016)
Objective To determine the effect of age on recurrence and progression rates in a population of high-risk non-muscle invasive bladder cancer (NMIBC) patients treated with a second transurethral resection (TUR) and at least 1 year of maintenance Bacillus Calmette-Guerin (BCG) therapy. Materials and Methods In this multicenter study, we reviewed the data of patients treated for high-risk NMIBC between 2005 and 2012. Patients without a muscle-invasive cancer on second TUR and received induction BCG and at least one year of maintenance BCG therapy and at least 12 months of follow-up after completion of maintenance BCG were included. Effect of age was analyzed both dichotomously (< 70 or >= 70 years) as well as by 10-year increments. Chi-square test, Student's T-test and analysis of variance (ANOVA) were used for comparison of the groups. Univariate and multivariate logistic regression analyses were performed to identify predictors of recurrence and progression. Results Overall, 242 eligible patients were included. Baseline parameters were similar. With a mean follow-up of 29.4 +/- 22.2 months, neither 3-year recurrence-free survival nor 3-year progression-free survival differed between the age groups when examined either dichotomously or by 10-year increments. Conclusion In high-risk NMIBC patients treated with a second TUR and received maintenance BCG therapy, age was not associated with increased rates of neither recurrence nor progression. Until a randomized prospective clinical trial assess the appropriate adjuvant intravesical therapy in the elderly, elderly patients should probably be treated in the same manner as younger patients.
Keywords: Bacillus Calmette Guerin; age; nonmuscle-invasive bladder cancer; second transurethral resection; RANDOMIZED CLINICAL-TRIAL; UROTHELIAL CARCINOMA; PROGNOSTIC-FACTORS; PROGRESSION RATES; RECURRENCE; SURVIVAL; EFFICACY